Leadership and the psychosocial work environment in old age care. (15th June 2015) - Lundgren, Dan; Ernsth‐Bravell, Marie; Kåreholt, Ingemar
Abstract : Aims and objectives: To study leadership factors and their associations with psychosocial work environmental among nursing assistants who are engaged in old age care and to analyse (i) differences in the assessment of leadership factors and the assessment of psychosocial work environmental in nursing homes and home help services and (ii) the association between the psychosocial work environment and factors that are related to leadership in nursing homes and home help services. Background: Leadership factors are an important element of the psychosocial work environment in old age care. The physical distance between leaders and nursing assistants is larger in home help services than in nursing homes. Therefore, it is important to study leadership separately in nursing homes and home help services. Design: Assessments from 844 nursing assistants in nursing homes and 288 in home help services (45 nursing homes and 21 home help service units) were analysed. Methods: The data were analysed using linear regression. Age, gender, number of staff at the unit, number of years at the current working unit and educational level were controlled in Model 1. Summarised indexes that were based on all independent variables except the main independent variable were additionally controlled in Model 2. Results: Psychosocial work environment was related to leadership factors, but stronger associations occurred more frequently in nursing homes than in home help services. Empowering leadership, support from superiors, the primacy of human resources and control over decisions were associated with higher assessments on all the variables that were related to the psychosocial work environment in both the nursing homes and home help services. Conclusions: Organisational differences in conducting leadership in old age care must be considered. Some leadership characteristics are better prerequisites for creating and maintaining a positive psychosocial work environment for nursing assistants in nursing homes and home help services. Implications for practice: Due to the differences in organisational settings, it is important to consider the differences in prerequisites in conducting leadership. To influence nursing assistants' performance and to increase quality in old age care in the long term, appropriate leadership is necessary.